2020
DOI: 10.1080/16184742.2020.1820062
|View full text |Cite
|
Sign up to set email alerts
|

Has UEFA’s financial fair play regulation increased football clubs’ profitability?

Abstract: Research question: In response to the low profitability of European football clubs, in 2010, UEFA established its Financial Fair Play regulation (FFP) to encourage clubs not to spend more than they earn. We examine whether FFP's break-even rule has increased the profitability of football clubs. Research methods: : We use data from the top five European football leagues (those of England, France, Germany, Italy, and Spain) over the period 2008-2016. Our sample includes 1,094 club-year observations (139 differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0
10

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(60 citation statements)
references
References 29 publications
1
43
0
10
Order By: Relevance
“…This study seeks to test the consequences of the FFP enforcement with regard to the break-even requirement. In line with previous studies (Ahtiainen and Jarva, 2020), we present two main hypotheses assuming the effectiveness of UEFA FFP both in terms of profitability and cost efficiency. From a 'profitability' perspective and considering the high financial distress in football (Plumley et al, 2021), we hypothesise that FFP has reduced clubs' losses.…”
Section: Research Hypothesessupporting
confidence: 64%
See 2 more Smart Citations
“…This study seeks to test the consequences of the FFP enforcement with regard to the break-even requirement. In line with previous studies (Ahtiainen and Jarva, 2020), we present two main hypotheses assuming the effectiveness of UEFA FFP both in terms of profitability and cost efficiency. From a 'profitability' perspective and considering the high financial distress in football (Plumley et al, 2021), we hypothesise that FFP has reduced clubs' losses.…”
Section: Research Hypothesessupporting
confidence: 64%
“…Franck (2018) also provided an economic analysis of FFP by providing plausible reasons about its contribution to the financial recovery observed in the first tiers of European football. Recently, Ahtiainen and Jarva (2020) conducted a study on the top five European football leagues to evaluate the impact of FFP on football clubs' profitability. A positive effect was found in Spain and there was weak evidence of such an improvement in England and Germany.…”
Section: Ffp: the Promise Of Enhanced Financial Health?mentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned, the revenues from player trading could be particularly relevant both for those teams with a smaller fan base and for those with a larger pool of supporters when the other sources of revenues are not sufficient to cover operating costs. Furthermore, clubs competing in the richest tournaments at the European level are subject to the UEFA financial fair play, which aims to make sure that the operating costs of professional football clubs are in line with their earnings (Ghio et al, 2018), although the benefits of its introduction are still debated (Ahtiainen & Jarva, 2020;Franck, 2018). In this framework, the ability to recognize and hire managers that are able to increase players' value may be the best choice in line with a profit-maximization strategy.…”
Section: Role Of Managers On Sport and Economic Performancementioning
confidence: 99%
“…A 2020 study on FFP's impact on club profitably found that "club revenues are 20% to 26% higher when the club reaches the quarterfinals or better [of the Champions League] after controlling for other factors". 114 This means that Real Madrid, along with other elite clubs who hold a financial advantage over their competitors, will continually find success in the Champions League and earn significantly greater revenue as a result.…”
Section: B Ffp As Restricting Competition By Effectmentioning
confidence: 99%